DIAGNOSTIC ANALYSIS OF COMMUNICATIVE COMPETENCE IN FOREIGN LANGUAGE TEACHING (Web of Teachers: Inderscience Research, 2026)
This article examines the importance of diagnosing communicative competence in the process of foreign language teaching. Communicative competence is considered a key component in developing learners’ ability to effectively use a foreign language in real-life situations. The study focuses on identifying the levels of learners’ linguistic, sociolinguistic, and pragmatic competences through diagnostic assessment methods. Various tools such as tests, observations, and interactive tasks are analyzed to evaluate students’ communicative performance. The results highlight the significance of systematic diagnostic analysis in improving teaching strategies, adapting instructional methods, and enhancing overall language proficiency. The paper also provides practical recommendations for teachers to implement effective diagnostic techniques in the classroom.